Toll-like receptor agonist induced changes in clonal rat BRIN-BD11 ß-cell insulin secretion and signal transduction - Kiely, A.; Robinson, A.; McClenaghan, N.; Flatt, P.; Newsholme, Philip (BioScientifica, 2009)
Evidence for involvement of toll-like receptors (TLRs) (e.g. TLR4 and TLR2, whose agonists include lipopolysaccharides (LPS) and saturated fatty acids) in altered patterns of signalling in adipose, liver and muscle from animal models of insulin resistance and obesity has been published. We have now extended this area of research and have determined the effects of LPS on cell viability, insulin secretion, insulin signalling and metabolism in a clonal b-cell line. BRIN-BD11 ß-cells were treated for 24 h with increasing concentrations of LPS. Chronic (24 h) and acute (20 min) insulin secretion, insulin content and parameters of cell metabolism and insulin signalling were determined. Incubation of BRIN-BD11 cells for 24 h in the presence of increasing concentrations of the TLR4 ligand LPS significantly decreased chronic (24 h) insulin secretion from 1.09±0.19 to 0.76±0.18 mg insulin/mg protein in the presence of 100 ng/ml LPS (P<0.05). There was no change in acute (20 min) stimulated insulin secretion or insulin content. Cell metabolism was not changed. Insulin receptor-ß (IRß) expression levels were increased significantly from 1±0.52 to 8.6±1.83 units (P<0.01), whereas calcineurin activity and Akt phosphorylation were significantly (P<0.01 and P<0.05 respectively) reduced in response to 24 h incubation in the presence of LPS. There was no change in IR substrate-1 protein expression or phosphorylation after 24 h. Further incubation for 24 h in the absence of LPS resulted in the recovery of chronic insulin secretion. The negative b-cell effects of LPS may contribute to hyperglycaemia in vivo. © 2009 Society for Endocrinology.